2011
DOI: 10.3109/03008207.2011.610476
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Articular Cartilage Degeneration after Application of Muscle Stretch

Abstract: The aim of study was to evaluate the progression of the ankle articular cartilage alterations after a post-immobilization muscle stretching. Twenty-nine Wistar rats were separated into five groups: C--control, S--stretched, SR--stretch recovery, IS--immobilized and stretched, and ISR--immobilized stretched recovery. The immobilization was maintained for 4 weeks and the left ankle was then stretched manually through a full dorsal flexion for 10 times for 60 s with a 30 s interval between each 60 s period, 7 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…29,38 In this context, our immunhistochemistry findings after 50 J∕cm 2 irradiation appeared to be a predictive factor for response to treatment. However, immuhistochemistry showed that, 8-weeks postsurgery, a higher expression of Col-1 was observed in control animals and laser treated animals, at 10 J∕cm 2 , suggesting a positive effect of the LLLT at 50 J∕cm 2 .…”
Section: Discussionmentioning
confidence: 69%
“…29,38 In this context, our immunhistochemistry findings after 50 J∕cm 2 irradiation appeared to be a predictive factor for response to treatment. However, immuhistochemistry showed that, 8-weeks postsurgery, a higher expression of Col-1 was observed in control animals and laser treated animals, at 10 J∕cm 2 , suggesting a positive effect of the LLLT at 50 J∕cm 2 .…”
Section: Discussionmentioning
confidence: 69%
“…Renner et al (28) and Dias et al (29) studied the effects of a muscle-stretching protocol after 4 weeks of immobilization of the ankle joint. Although their analysis of cartilage thickness and the number of chondrocytes was conducted in different regions, the authors found no differences in the thickness of the articular cartilage between the groups, as in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have affirmed that OA articular cartilage displays fewer organized networks and that collagen content falls in advanced OA compared to early OA articular cartilage, especially type II [21,28,[41][42][43]. In this study, the Picro-sirius polarization method was not able to show any collagen modification by comparing the results found in the intact and injured animals.…”
Section: Discussionmentioning
confidence: 47%